Perspectives of healthcare providers on withdrawal of life-sustaining treatment and advanced directives for unresponsive wakefulness syndrome in China - Li, Meiqi; Dai, Siyu; Wang, Le; Di, Haibo (Frontiers in Neurology, 2024)
Objectives We performed the current research to describe healthcare providers’ perspectives toward withdrawal of life-sustaining treatment (WLST) and advanced directive (AD) of patients with unresponsive wakefulness syndrome (UWS) and to identify influencing factors of their perspectives. Methods Healthcare providers were recruited during a professional conference on disorders of consciousness (DoC). Participants completed self-administered questionnaires which included demographics, personal perspectives regarding WLST and the perception of ADs. Results A total of 230 Chinese healthcare providers (female: 69.7%) were included. Only a small proportion reported positive attitudes toward withdrawing artificial nutrition and hydration (35.2%), antibiotics (30.9%), and do-not-resuscitation orders (23.5%) in UWS patients. As for predictors’ identification, religion was significantly associated with the positive attitude toward DNR order (p = 0.004). Moreover, although 47.4% of the participants had never heard of ADs before of conference, almost all of them would consider ADs (95.7%) thereafter, especially for non-neurologists (p = 0.033). Conclusion The propensity to WLST for UWS in China is low and perspective on WLST is significantly associated with individual characteristics. The attitudes of healthcare providers toward integrating ADs in the decisional process are positive. Future research regarding ADs and their predictors should be carried out to improve the quality of end-of-life care of UWS in China.